APLIKASI SISTEM INFORMASI PERSEDIAAN (INVENTORY) BARANG BERBASIS WEB STUDI KASUS: PT. BINA KARYA - Alan Pustawan (Ensiklopedia of Journal, 2019)
PT. Bina Karya is a company engaged in sales of household appliances such as a clothesline clothes rack, plate and aluminum ladder. The development of technology and supported by the development of software or hardware that is more advanced and will help facilitate the processing of data out of incoming goods so that effectiveness and efficiency in the company's performance can be achieved. Currently, implemtasinya in the field face major obstacles when the system out of the incoming goods in the warehouse, so on PT. Community development work in processing systems out of incoming goods are not directional and organized so that the function and purpose of information security as well as an influx of irregular goods out. Preparation of incoming goods out system is an activity consisting of data receipt of goods, sales data item, return data as well as data on stock items that reported all activities out of the incoming goods in the PT. Bina in Work per day or per month. The purpose of this research is to make the design of the computerized system applications out of the incoming goods efficiently and create the PHP programming language into implemtasinya. The result of this writing is able to assist and expedite the processing of incoming goods data out as well as the supervision of the incoming goods flow out so penyamapaian information more effectively and efficiently.